Effects of a Commercial Microbial Agent on the Bacterial Communities in Shrimp Culture System - Liu, Zidan; Qiuqian, Linglin; Yao, Zhiyuan; Wang, Xin; Huang, Lei; Zheng, Jialai; Wang, Kai; Li, Laiguo; Zhang, Demin (Frontiers in Microbiology, 2018)
Commercial microbial agents (e.g. probiotics, microbial products, microorganism preparation et al.) have been widely applied for disease control in shrimp culture. However, the effect of these microbial agents (MA) on shrimp health is unstable and the underlying mechanism remains unclear. The effect of MA can probably be achieved by influencing the bacterial community of shrimp culture system. To test this hypothesis, we used 16S rRNA gene amplicon sequencing to investigate the dynamics of both planktonic and intestinal bacterial composition in shrimp culture ponds with or without commercial MA applied weekly. The results showed that MA application increased the temporal turnover rate of bacterioplankton community. Within one week, MA-treatment significantly drove bacterioplankton community composition to divert from that without MA-treatment at day 2 after MA application, but the deviation tended to vanish at day 4 and day 7. At day 21, a significant difference was observed in shrimp intestinal bacterial community between two groups. The relative abundance of Rhodobacteraceae in shrimp intestine was significantly greater in the MA-treated group than that in the control. However, MA-treatment did not significantly improve the growth or survival ratio of shrimp. This study suggest that MA works in terms of accelerating bacterioplankton community turnover and shifting intestinal bacterial community; however, its effect on shrimp growth might vary greatly and might be improved by optimizing the method in activation and application and more investigation on the microbial ecological process of shrimp culture system is needed before we develop and apply probiotics more efficiently.